An oxide solid electrolyte film for an all-solid battery and a method for manufacturing the same
Patent Information
- Application Number
- CN202611010811.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明提供一种全固态电池用氧化物固态电解质膜的制备方法,能有效抑制电解质与承烧板界面粘连、不损害电解质本征性能(晶体结构、离子电导率等)且适配氧化物固态电解质膜的高温烧结工艺的技术方案,旨在解决氧化物电解质在高温烧结过程中与承烧板发生界面粘连、元素互扩散以及由此导致的性能劣化问题
1.本发明采用不同粒径的LLZO粉体构建多层结构,显著降低烧结风险提升烧结质量。在高温烧结过程中,该粒径梯度结构可作为应变缓冲层,对高温烧结时因温度空间差异而产生的变形趋势进行协调,减轻电解质整体的翘曲和开裂倾向。此外,本发明的第二膜带设计犹如在电解质与承烧板之间铺设隔离层,使样品与承烧板在烧结过程中保持物理分隔,避免两者直接接触,防止样品在高温下与承烧板发生粘连,从而有效提高烧结成品率。
Smart Images

Figure CN122931067A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and in particular to an oxide solid electrolyte membrane for all-solid-state batteries and its preparation method. Background Technology
[0002] Against the backdrop of a global strategic shift towards a clean and low-carbon energy structure, solid-state lithium batteries, which combine high safety and high energy density, have become a cutting-edge research hotspot and a core development direction in the field of power batteries. Traditional liquid lithium-ion batteries suffer from defects such as easy leakage and flammability of the electrolyte, severely limiting their industrialization in high-end applications such as new energy vehicles and large-scale energy storage. Solid-state lithium batteries replace traditional liquid electrolytes with solid electrolytes. This not only fundamentally solves the problems of electrolyte leakage and thermal runaway but also allows for compatibility with metallic lithium anodes, significantly improving battery energy density, thus becoming a research hotspot and core development direction in the lithium battery field.
[0003] Among numerous solid electrolyte materials, garnet-type Li7La3Zr2O 12 (LLZO) oxide electrolytes possess high room-temperature lithium-ion conductivity, reaching up to 10. -3 ~10 -4 S·cm -1 ), wide electrochemical stability window (0-5V vs Li) + Due to its excellent chemical stability and compatibility with lithium metal, LLZO electrolyte is considered one of the most promising solid-state electrolytes. However, the preparation process of LLZO electrolyte still faces many challenges, among which high-temperature sintering is the key step that determines its density, crystal structure integrity, and ion conductivity. To obtain LLZO electrolytes with high density and low defects, long-term sintering at high temperatures of 1000–1400℃ is usually required to promote mass transfer and densification between particles.
[0004] During high-temperature sintering, LLZO green bodies need to be placed on a sintering plate for heat treatment. Commonly used sintering plates include alumina (Al₂O₃), zirconium oxide (ZrO₂), magnesium oxide (MgO), and boron nitride (BN). Ideally, the sintering plate should only serve a load-bearing function, maintaining physical isolation from the LLZO green body to avoid chemical or physical interactions. However, in actual sintering, adhesion easily occurs between the LLZO oxide electrolyte and the sintering plate. Specifically, a strong bonding layer forms between the sintered LLZO ceramic body surface and the sintering plate surface. External force is required during demolding, severely damaging the surface integrity and internal dense structure of the oxide electrolyte, easily inducing sample breakage, and significantly reducing product yield. Simultaneously, interfacial contaminants generated by adhesion adhere to the sintering plate surface, impairing its reusability and increasing manufacturing costs and process complexity. More seriously, interdiffusion or chemical reactions may occur at the adhesion interface, generating impurity phases such as Li-Al-O and Li-Zr-O, which disrupt the garnet crystal structure of LLZO, significantly reduce its lithium-ion conductivity, and deteriorate the interfacial impedance and cycle stability of all-solid-state lithium batteries. Existing anti-adhesion technologies, such as modified sintering plate coatings and interfacial separators, have significant compatibility defects and are difficult to effectively solve the interfacial adhesion problem during the high-temperature sintering process of oxide electrolytes.
[0005] In summary, existing technologies have not yet effectively overcome the interfacial adhesion problem between oxide electrolytes and the sintering plate during high-temperature sintering. This problem directly restricts the industrial application of oxide electrolytes, thereby hindering the commercialization and promotion of solid-state lithium battery technology. Therefore, developing a technical solution adapted to the high-temperature sintering process of oxide electrolytes, effectively suppressing interfacial adhesion without compromising the intrinsic properties of the electrolyte, is of significant academic value and practical importance for promoting the industrialization of solid-state lithium batteries. This application proposes a corresponding solution accordingly. Summary of the Invention
[0006] This invention provides a method for preparing an oxide solid electrolyte membrane for all-solid-state batteries. It is a technical solution that can effectively suppress the adhesion between the electrolyte and the sintering plate, without damaging the intrinsic properties of the electrolyte (crystal structure, ionic conductivity, etc.) and is compatible with the high-temperature sintering process of oxide solid electrolyte membranes. It aims to solve the problems of interface adhesion, element interdiffusion, and performance degradation caused by oxide electrolytes and the sintering plate during high-temperature sintering.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This invention provides a method for preparing an oxide solid electrolyte membrane for all-solid-state batteries, comprising the following steps: S1. Preparation of LLZO first powder: Lithium source, lanthanum source, zirconium source and dopant were weighed according to the stoichiometric ratio of LLZO and added to a ball mill jar. Isopropanol was added as a grinding aid. The mixture was ball milled at 200-600 rpm / min for 12-36 hours to achieve uniform distribution of the reactants at the microscale. The powder was then dried at 60-80℃ for 12 hours. The dried powder was calcined at 800-1200℃ for 6-12 hours and then ball milled again at 300-600 rpm to obtain LLZO first powder with a small particle size and uniform distribution, with a particle size of 0.1μm-5μm. S2. Preparation of LLZO second powder: Lithium source, lanthanum source, and zirconium source were weighed into a ball mill jar according to the stoichiometric ratio of LLZO. Isopropanol was added as a grinding aid, and the mixture was ball-milled at a speed of 200-600 rpm / min for 12-36 hours to achieve uniform distribution of the reactants at the microscale. The powder was then dried at 60-80℃ for 12 hours. The dried powder was calcined at 800-1200℃ for 6-12 hours, followed by secondary sintering and ball milling to obtain LLZO second powder with a particle size of 1μm-50μm. S3. Preparation of the first film strip: Mix LLZO first powder, sintering aid, first dispersant, first solvent, first binder and first plasticizer into a slurry, coat it on the substrate and remove part of the solvent to obtain the first film strip; S4. Preparation of the second film strip: Mix the second LLZO powder, the second dispersant, the second solvent, the second binder and the second plasticizer into a slurry, coat it on the substrate and remove part of the solvent to obtain the second film strip; S5. Preparation of multilayer oxide electrolyte preform: The first film strip is used as the middle layer, and the second film strips are symmetrically arranged on both sides. The multilayer oxide electrolyte preform is hot-pressed to form a homogeneous and dense multilayer composite structure. S6. High-temperature sintering: The multilayer oxide electrolyte blank is placed between two sintering plates and sintered at 800℃~1200℃ to allow the material to undergo grain growth and densification. After cooling, a multilayer oxide solid electrolyte membrane is obtained. S7. Post-processing: Polishing is performed on the multilayer oxide solid electrolyte membrane.
[0008] As a preferred technical solution, the polishing process in step S7 involves partially removing the outer layer of the second membrane strip, so that the surface of the final oxide solid electrolyte membrane retains a residual layer of the second membrane strip with a thickness of 1 μm to 10 μm.
[0009] As a preferred technical solution, the dopant in step S1 includes one or more of Ta, B, Nb, Ga, Al, W, and Ca.
[0010] As a preferred technical solution, the temperature of the secondary sintering in step S2 is 600℃~1200℃.
[0011] As a preferred technical solution, the sintering aid in step S3 includes one or more of the following: Li2O, Li2CO3, LiNO3, LiF, Li3PO4, LiBO2, Li2B4O7, ZnO, MgO, SiO2, and B2O3.
[0012] As a preferred technical solution, the hot pressing temperature in step S5 is 60℃~120℃, and the pressure is 5MPa~400MPa.
[0013] As a preferred technical solution, the lithium source in steps S1 and S2 includes one or more of lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium citrate, and lithium acetate.
[0014] As a preferred technical solution, the lanthanum source in steps S1 and S2 includes one or more of lanthanum oxide, lanthanum nitrate, lanthanum hydroxide, and lanthanum carbonate.
[0015] As a preferred technical solution, the zirconium source in steps S1 and S2 includes one or more of zirconium dioxide, zirconium nitrate, and zirconium carbonate.
[0016] As a preferred technical solution, the first solvent in step S3 and the second solvent in step S4 include one or more of methanol, ethanol, isopropanol, acetone, cyclohexanone, butanone, toluene, and xylene.
[0017] As a preferred technical solution, the first adhesive in step S3 and the second adhesive in step S4 include one or more of the following: polypropylene, methyl methacrylate, polyacrylonitrile, polyvinylidene fluoride, polyisobutylene, styrene-butadiene rubber, polyacrylic acid, polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl acetal resin, polyvinyl butyral, and polyethylene oxide.
[0018] As a preferred technical solution, the first dispersant in step S3 and the second dispersant in step S4 include one or more of fish oil, triethanolamine, polyethylene glycol, polyvinylpyrrolidone, ethylene glycol monobutyl ether, and tributyl citrate.
[0019] As a preferred technical solution, the first plasticizer in step S3 and the second plasticizer in step S4 include one or more of the following: dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate, polyethylene glycol, diisononyl phthalate, tributyl acetyl citrate, and tributyl citrate.
[0020] As a preferred technical solution, the thickness of the first film strip prepared in step S3 is 10μm to 200μm.
[0021] As a preferred technical solution, the material of the firing plate includes one or a combination of two of the following: platinum, palladium, copper, aluminum, nickel, alumina, porous alumina, zirconium oxide, porous zirconium oxide, magnesium oxide, or porous magnesium oxide.
[0022] Another aspect of the present invention is to provide an oxide solid electrolyte membrane prepared by the above method. The electrolyte membrane has a three-layer gradient structure, wherein the middle layer is formed by sintering dense LLZO first powder, and the two surface layers are composed of residual layers formed by sintering LLZO second powder.
[0023] The beneficial effects of this invention are: 1. This invention employs LLZO powders of varying particle sizes to construct a multi-layer structure, significantly reducing sintering risks and improving sintering quality. During high-temperature sintering, this particle size gradient structure acts as a strain buffer layer, coordinating the deformation trends caused by temperature differences during high-temperature sintering and mitigating the overall warping and cracking tendency of the electrolyte. Furthermore, the second membrane strip design of this invention functions as an isolation layer between the electrolyte and the sintering plate, maintaining physical separation between the sample and the sintering plate during sintering, preventing direct contact, and preventing the sample from sticking to the sintering plate at high temperatures, thereby effectively improving the sintering yield.
[0024] 2. This invention introduces a sintering aid into the first membrane strip. This aid can promote particle rearrangement and accelerate diffusion mass transfer to fill pores at high temperatures. Therefore, this invention can achieve a highly dense, low-porosity structure, thereby improving the continuity of lithium-ion migration and grain boundary conductivity, and thus enhancing the overall ionic conductivity of the electrolyte.
[0025] 3. This invention reduces interfacial reactions through structural design, thereby maintaining the stability of the LLZO garnet crystal structure and ensuring a stable lithium-ion migration path. Since the lithium-ion diffusion path of garnet-type LLZO is a three-dimensional framework channel structure, the lithium-ion migration barrier is low when the lattice remains intact. Therefore, this invention can maintain a high room-temperature ionic conductivity.
[0026] 4. The structural design and process method proposed in this invention have a wide range of applicability, strong applicability of the firing materials, the ability to scale up the casting process, and improved firing pass rate. Attached Figure Description
[0027] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0028] Figure 1 A schematic diagram illustrating the oxide solid electrolyte membrane preparation process in an embodiment of the present invention is shown; Figure 2 A schematic diagram illustrating the preparation of a multilayer oxide solid electrolyte membrane according to an embodiment of the present invention is shown; Figure 3 The cross-sectional SEM image of the oxide solid electrolyte membrane of Example 4 is shown.
[0029] In the figure, 100 is the magnesium oxide sintering plate; 101 is the second film strip; and 102 is the first film strip. Detailed Implementation
[0030] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art.
[0031] Example: Preparation of Ta-doped Li 6.4 La3Zr 1.4 Ta 0.6 O 12 The following raw materials were weighed according to the stoichiometric ratio and a 15% lithium source excess for the (LLZTO) oxide electrolyte: lithium hydroxide (LiOH), lanthanum oxide (La₂O₃), zirconium oxide (ZrO₂), and tantalum oxide (Ta₂O₅). These raw materials were placed in an agate ball mill jar, and zirconium oxide grinding beads and isopropanol were added. The mixture was wet-milled at 500 rpm for 10 h. The homogeneous powder was then dried in an oven at 80 °C for 12 h to remove the isopropanol solvent. The dried powder was then calcined in a muffle furnace at 950 °C for 6 h. The sintered powder was then placed in an agate ball mill jar, and zirconium oxide grinding beads and isopropanol were added. The mixture was ball-milled at 500 rpm for 24 h, and then dried in an oven to obtain LLZTO powder with a particle size of 700 nm.
[0032] To prepare Li7La3Zr2O 12(LLZO) oxide electrolyte was prepared by weighing the following raw materials according to stoichiometric ratio: lithium hydroxide (LiOH), lanthanum oxide (La₂O₃), and zirconium oxide (ZrO₂). The raw materials were placed in an agate ball mill jar, and zirconium oxide grinding beads and isopropanol were added. The mixture was wet-milled at 500 rpm for 10 hours. The homogeneous powder was then dried in an oven at 80°C for 12 hours to remove the isopropanol solvent. The dried powder was then calcined in a muffle furnace at 950°C for 6 hours to obtain LLZO powder.
[0033] In subsequent embodiments, the LLZTO powder and LLZO powder prepared above were used as starting materials.
[0034] Example 1: Preparation of oxide solid electrolyte membrane, including the following steps.
[0035] Step 1: Weigh 140g of LLZO powder and place it in a magnesium oxide crucible. Put the crucible into a muffle furnace and sinter it at high temperature in air. The sintering conditions are: heating rate 10℃ / min; holding temperature 950℃; holding time 12h. After cooling, the LLZO powder after secondary sintering is obtained. Put the powder into an agate ball mill jar, add zirconia grinding beads and isopropanol, and wet ball mill at 300rpm / min for 4h to obtain 2µm LLZO powder (second powder).
[0036] Step 2: Preparation of the first film strip. Weigh out 0.77% fish oil, 34.66% LLZTO powder, 24.8% isopropanol, 24.8% toluene, 6.22% polyvinyl butyral (PVB), 7.75% dibutyl phthalate (DBP), and 1% LiBO2 raw materials according to the specified mass ratio. Add these to a mixing tank and stir for 28 hours to obtain a slurry. Then, use a blade coating method to coat the slurry onto a PET substrate. After drying the solvent, a first film strip with a thickness of 200 μm is obtained.
[0037] Step 3, Preparation of the second membrane strip: except that the LLZTO powder is replaced with LLZO powder after secondary sintering, the same steps and conditions as in step 2 are used to obtain a second membrane strip with a thickness of 20 μm. Step 4: Place the second membrane strip on both sides of the first membrane strip and hot-press it at 200 MPa and 80°C for 10 minutes to obtain a multilayer oxide electrolyte preform with a thickness of 200 μm. Figure 2 As shown.
[0038] Step 5: The hot-pressed multilayer film strip is placed between two magnesium oxide sintering plates and placed in an oxygen atmosphere furnace. The temperature is increased to 650℃ at a rate of 1℃ / min and held for 2 hours. Then, the temperature is changed to an argon atmosphere and increased to 1100℃ at a rate of 10℃ / min, held for 6 hours. After cooling, a multilayer oxide solid electrolyte membrane is obtained. After grinding and polishing, an oxide solid electrolyte membrane is obtained.
[0039] Example 2: In this example, except that the particle size of LLZO powder is adjusted to 5 μm, the oxide electrolyte is obtained using the same steps and conditions as in Example 1.
[0040] Example 3: In this example, except that the particle size of LLZO powder is adjusted to 10 μm, the oxide solid electrolyte membrane is obtained using the same steps and conditions as in Example 1.
[0041] Example 4: In this example, except that the thickness of the second membrane strip is adjusted to 40 μm, the oxide solid electrolyte membrane is obtained using the same steps and conditions as in Example 3.
[0042] Example 5: In this example, except that the thickness of the second membrane strip is adjusted to 60 μm, the oxide solid electrolyte membrane is obtained using the same steps and conditions as in Example 3.
[0043] Example 6: In this example, except that the thickness of the second membrane strip is adjusted to 80 μm, the oxide solid electrolyte membrane is obtained using the same steps and conditions as in Example 3.
[0044] Example 7: In this example, except that the thickness of the second membrane strip is adjusted to 100 μm, the oxide solid electrolyte membrane is obtained using the same steps and conditions as in Example 3.
[0045] For the comparative example and preparation of the oxide solid electrolyte membrane, the first membrane strip was first hot-pressed at 200 MPa and 80 °C for 10 min to obtain an oxide electrolyte preform with a thickness of 200 μm. Then, the hot-pressed first membrane strip was placed between two magnesium oxide sintering plates and placed in an oxygen atmosphere furnace, heated to 650 °C at a heating rate of 1 °C / min and held at that temperature for 2 h. Then, the temperature was changed to an argon atmosphere, heated to 1100 °C at a heating rate of 10 °C / min and held at that temperature for 6 h, and then cooled to obtain the oxide solid electrolyte membrane.
[0046] The ease of separation between the oxide solid electrolyte membrane and the magnesium oxide sintering plate prepared according to the above examples and comparative examples was evaluated. The evaluation results of Examples 1-7 and comparative examples are summarized in the table.
[0047]
[0048] SEM analysis was performed on the oxide electrolyte, and cross-sectional SEM analysis was performed on the oxide solid electrolyte membrane obtained by grinding and polishing. The cross-sectional SEM image of the oxide solid electrolyte membrane in Example 4 is shown below. Figure 3 As shown.
[0049] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A method for preparing an oxide solid electrolyte membrane for all-solid-state batteries, characterized in that, Includes the following steps: S1. Preparation of LLZO first powder: Lithium source, lanthanum source, zirconium source and dopant were weighed according to the stoichiometric ratio of LLZO and added to a ball mill jar. Isopropanol was used as a grinding aid for ball milling and mixing. The dried powder was calcined at 800℃~1200℃ and then ball milled to obtain LLZO first powder with a particle size of 0.1μm~5μm. S2. Preparation of LLZO second powder: Weigh lithium source, lanthanum source and zirconium source into ball mill jar according to the stoichiometric ratio of LLZO, and mix them by ball milling with isopropanol as grinding aid. The dried powder is calcined at 800℃~1200℃, and then refined by secondary sintering and ball milling to obtain LLZO second powder with a particle size of 1μm~50μm. S3. Preparation of the first film strip: Mix LLZO first powder, sintering aid, first dispersant, first solvent, first binder and first plasticizer into a slurry, coat it on the substrate, and remove part of the solvent to obtain the first film strip; S4. Preparation of the second film strip: Mix the second LLZO powder, the second dispersant, the second solvent, the second binder and the second plasticizer into a slurry, coat it on the substrate, and remove part of the solvent to obtain the second film strip; S5. Preparation of multilayer oxide electrolyte preform: The first film strip is used as the middle layer, and the second film strips are symmetrically arranged on both sides of it. The multilayer oxide electrolyte preform is obtained by hot pressing. S6. High-temperature sintering: The multilayer oxide electrolyte blank is placed between two sintering plates and sintered at 800℃~1200℃. After cooling to room temperature, a multilayer oxide solid electrolyte membrane is obtained. S7. Post-processing: Polishing is performed on the multilayer oxide solid electrolyte membrane.
2. The method for preparing the oxide solid electrolyte membrane according to claim 1, characterized in that, In step S7, the polishing process involves partially removing the outer layer of the second membrane strip, leaving a residual layer of the second membrane strip with a thickness of 1 μm to 10 μm on the surface of the final oxide solid electrolyte membrane.
3. The method for preparing the oxide solid electrolyte membrane according to claim 1, characterized in that, The dopant in step S1 includes one or more of Ta, B, Nb, Ga, Al, W, and Ca.
4. The method for preparing the oxide solid electrolyte membrane according to claim 1, characterized in that, The temperature for the secondary sintering in step S2 is 600℃~1200℃.
5. The method for preparing an oxide solid electrolyte membrane according to claim 1, characterized in that, The sintering aids in step S3 include one or more of the following: Li2O, Li2CO3, LiNO3, LiF, Li3PO4, LiBO2, Li2B4O7, ZnO, MgO, SiO2, and B2O3.
6. The method for preparing an oxide solid electrolyte membrane according to claim 1, characterized in that, The hot pressing temperature in step S5 is 60℃~120℃, and the pressure is 5MPa~400MPa.
7. The method for preparing an oxide solid electrolyte membrane according to claim 1, characterized in that, The lithium source in steps S1 and S2 includes one or more of lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium citrate, and lithium acetate. The lanthanum source in steps S1 and S2 includes one or more of lanthanum oxide, lanthanum nitrate, lanthanum hydroxide, and lanthanum carbonate. The zirconium source in steps S1 and S2 includes one or more of zirconium dioxide, zirconium nitrate, and zirconium carbonate.
8. The method for preparing an oxide solid electrolyte membrane according to claim 1, characterized in that, The first solvent in step S3 and the second solvent in step S4 include one or more of methanol, ethanol, isopropanol, acetone, cyclohexanone, butanone, toluene, and xylene; The first adhesive in step S3 and the second adhesive in step S4 include one or more of the following: polypropylene, methyl methacrylate, polyacrylonitrile, polyvinylidene fluoride, polyisobutylene, styrene-butadiene rubber, polyacrylic acid, polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl acetal resin, polyvinyl butyral, and polyethylene oxide. The first dispersant in step S3 and the second dispersant in step S4 include one or more of fish oil, triethanolamine, polyethylene glycol, polyvinylpyrrolidone, ethylene glycol monobutyl ether, and tributyl citrate; The first plasticizer in step S3 and the second plasticizer in step S4 include one or more of dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate, polyethylene glycol, diisononyl phthalate, tributyl acetyl citrate, and tributyl citrate.
9. The method for preparing an oxide solid electrolyte membrane according to claim 1, characterized in that, The thickness of the first membrane strip prepared in step S3 is 10 μm to 200 μm.
10. The oxide solid electrolyte membrane prepared by the method according to any one of claims 1-9, characterized in that, The electrolyte membrane has a three-layer gradient structure, with the middle layer being formed by sintering dense LLZO first powder, and the two surface layers being residual layers formed by sintering LLZO second powder.